Uji Aktivitas Ekstrak Daun Dan Akar Singawalang (Petiveria alliaceae) Terhadap Penghambatan Tirosinase - Sholikha, Munawarohthus; M, R., Nur; M, R., Nur; A.R., Mahfudza, (Jurnal Farmasi Udayana, 2021)
Tyrosinase is an enzyme that plays a role in the formation of skin pigments from a person because it is involved in the process of melanogenesis. Tyrosinase plays a very important role in the skin depigmentation process, there are several attempts to inhibit the skin depigmentation process, one of which is by inhibiting tyrosinase. Research on the leaves and roots of singawalang (Petiveria alliacea) was conducted to determine the potential as a tyrosinase inhibitor. Leaves and root extracts of singawalang were macerated with ethanol, then tested for identification of secondary metabolites. Singawalang leaves extract contains alkaloids, tannins and terpenoids while singawalang root extract contains alkaloids, flavonoids, tannins and terpenoids. Tyrosinase inhibitory activity used the microplate reader ELISA technique at a wavelength of 492 nm. Tests were carried out on kojic acid as a comparison and L-DOPA as a substrate. The results of the tyrosinase inhibition activity test for the extracts of singawalang leaves, singawalang roots and kojic acid, IC 50 were 9.817 mg / mL, 4.987 mg / mL and 0.092 mg / mL, respectively.